Teaching Practitioner Program Evaluation at the Banten College of Administrative Science - Sonjaya, Trisna; Lutfi, Lutfi (Akademika : Jurnal Teknologi Pendidikan, 2025)
The aim of evaluating the Teaching Practitioner Program at the Banten College of Administrative Sciences using the CIPP Model. The ultimate goals of the teaching practitioner program are: 1) reduce the gap between the skills of college graduates and industry needs; 2) increase the competitiveness of graduates in the global labor market; 3) building an adaptive and collaborative educational ecosystem between the world of education and industry; and 4) provide students with direct insight into real challenges in the world of work as well as the latest technology that is being developed. The research approach by quantitative descriptive method to evaluate program. The results of research evaluating the teaching practitioner program at the Banten College of Administrative Sciences obtained an average rating of 75% (very good). The results of the evaluation of the teaching practitioner program using the CIPP Evaluation Model are: (1) the results of the context evaluation show that program participants are able to understand the objectives of the teaching practitioner program with a very good assessment (79%); (2) the results of the input evaluation show that the input aspect of the teaching practitioner program at the STIA Banten campus is rated very well (74%); (3) the results of the process evaluation show that the implementation dimensions of the teaching practitioner program at STIA Banten are running very well (71%); and (4) the product evaluation results show that the product implications of fulfilling the main performance indicator achievements (IKU 4, namely: on-campus teaching practitioners and IKU 7 achievements, namely: collaboration classes) at STIA Banten were implemented very well (76%).